Comparative study of somatic and motor characteristics of the best athletes at one mile discipline outdoor all time - Ivan, P.; Gheorghe, D. (Journal of Sport and Kinetic Movement, 2017)
The research is part of the study of sport performance, measurement and evaluation. It has a transverse type because the collected results were obtained by 31 December 2016. The aim of this research was to observe the dynamics of the parameters mentioned below, worthy of being taken into account in the selection of athletes. Material and methods: This study analyzes the results, age, height and weight of the best athletes at one mile discipline outdoor all time. Data were processed on the following statistical indicators: number of cases, the maximum value, minimum value, amplitude, mode, median, average, quartile 1, 3, quartile difference, dispersion, average of absolute deviation, standard deviation, coefficient of variation and correlation. As a research method we had used the case study, observation, statistics and graphics. Results: After data processing had resulted 2 summary tables and 4 graphs. Discussions and conclusions: The results were analyzed based on the above parameters. This resulted in the following conclusions: - The average performance is 3:49:36 for men and 4:19:16 for women - The average age is 25.63 years for men and 27.15 years for women. - The average height is 179.01 cm for men and 167.11 cm for women. - The average weight is 64.21 kg for men and 52.08 kg for women.